Alarming Low Adherence to the 24-Hour Movement Behavior in Adolescents - the Cogni-Action Project - De Moraes-Ferrari, G (FRONTIERS MEDIA SA, 2025)
Background Unhealthy movement behaviors are a critical concern, particularly in developing countries and regions like Latin America. Evaluating adherence to the 24-Hour Movement Behavior (24-HMB) through a combination of objective and self-reported measures of moderate-to-vigorous physical activity (MVPA), adequate sleep duration (SD), and limited sedentary time (ST) is essential for understanding the interplay among these behaviors during adolescence.Objective This cross-sectional study aimed to assess adherence to the 24-HMB among Chilean adolescents aged 10-14 years and explore differences by age and sex.Methods A total of 359 participants (53.48% girls) wore accelerometers to objectively measure compliance with the recommended 60 min of MVPA per day, as well as appropriate SD (9-11 h for ages 10-13 and 8-10 h for age 14). ST was assessed through self-reported data (<= 2 h/day).Results Compliance with the MVPA, SD, and ST recommendations was achieved by 0.84, 4.74, and 70.47% of participants, respectively. When combining guidelines, only 0.56% of participants met both the ST and MVPA recommendations, while 3.90% adhered to both the ST and SD recommendations. Notably, no participants met both the SD and MVPA guidelines, nor did any fulfill all three movement guidelines. Finally, no significant differences were observed by sex or age.Conclusion These findings underscore the alarmingly low adherence to the 24-HMB among this sample of adolescents, highlighting the urgent need for targeted public health interventions. The study advocates for policymakers to adopt an integrated approach to promote healthy behaviors, addressing them collectively rather than in isolation.